The Antidepressant-Like Activity of the New Tetrapeptide Neuroprotector Kk-1, Homologous of Acth15-18 Sequence (An Experimental Study) - Roman D. Deiko; Sergiy Yu. Shtrygol; Alexandr A. Kolobov; Andrey S. Simbirtsev; Maria V. Mishchenko (Journal of Depression And Therapy, 2017)
Theaim of study is to evaluate antidepressant-like activity of the new peptidergic neuroprotectoracetyl-(D-Lys)-Lys-Arg-Arg-amide, homologous of ACTH15-18 primary amino acids sequence, that demonstrates nootropic and neuroprotective properties. Using Porsolt swimming test (PST) efficacy of tetrapeptide neuroprotector KK-1 at a single dose of 0.02 mg/kg was investigated on 16 white random bred male rats (body mass equaled 180-220 grams). Imipramine (15 mg/kg i.p.) was used as a reference drug. Then depression was induced in these rats by reserpine (4 mg/kg, i.p.). The KK-1 (intranasally, i.n.) and imipramine were administered once a day during 3 days until the reserpine-induced depression was reproduced. The indices of rats behavior under the conditions of open-field test (OFT) and PST were evaluated. The influence of both drugs on specific reserpine-induced depressions symptoms (hypothermia and blepharoptosis) was also registered. The results were processed statistically. The tetrapeptide neuroprotector KK-1 reduced immobilization time of rats at PST (statistically significant differences compared with control group), exceeding efficacy of reference drug imipramine. Normalizing of locomotor and exploratory activity in the OFT, decreasing indices of rats helplessness behavior in PST by tetrapeptide neuroprotector KK-1 demonstrates its antagonism with depressive action of reserpine. The tetrapeptide KK-1 showed antidepressant-like action both in intact rats and in rats with the model of reserpine-induced depression. It reduced specific symptoms of depression – hypothermia and blepharoptosis, exceeding the activity of reference drug imipramine.
Keywords: oligopeptide